A golden grave - Lindsey, Erin (Lindsey, Erin. Rose Gallagher mystery., 2019)
Rose Gallagher always dreamed of finding adventure, so her new life as a freshly-minted Pinkerton agent ought to be everything she ever wanted. Only a few months ago, she was just another poor Irish housemaid from Five Points; now, she's learning to shoot a gun and dance the waltz and throw a grown man over her shoulder. Better still, she's been recruited to the special branch, an elite unit dedicated to cases of a paranormal nature, and that means spending her days alongside the dashing Thomas Wiltshire. But being a Pinkerton isn't quite what Rose imagined, and not everyone welcomes her into the fold. Meanwhile, her old friends aren't sure what to make of the new Rose, and even Thomas seems to be having second thoughts about his junior partner. So when a chilling new case arrives on Rose's doorstep, she jumps at the chance to prove herself - only to realize that the stakes are higher than she could have imagined. Six delegates have been murdered at a local political convention, and the police have no idea who - or what - is responsible. One thing seems clear: The killer's next target is a candidate for New York City mayor, one Theodore Roosevelt. Convinced that something supernatural is afoot, Rose and Thomas must track down the murderer before Roosevelt is taken out of the race - permanently. But this killer is unlike any they've faced before, and hunting him down will take them from brownstones to ballrooms to Bowery saloons. Not quite comfortable anywhere, Rose must come to terms with her own changed place in society - and the fact that some would do anything to see her gone from it entirely.